Eicosapentaenoic acid (EPA) production by an oleaginous fungus Mortierella alpina expressing heterologous the Δ17‐desaturase gene under ordinary temperature. Issue 12 (23rd June 2015) - Okuda, Tomoyo; Ando, Akinori; Negoro, Hiroaki; Muratsubaki, Tatsuya; Kikukawa, Hiroshi; Sakamoto, Takaiku; Sakuradani, Eiji; Shimizu, Sakayu; Ogawa, Jun
Abstract: The oleaginous fungus Mortierella alpina is known to accumulate eicosapentaenoic acid (EPA) only when cultivated at a low temperature (below 15°C). Here, we investigated EPA production at an ordinary temperature (28°C) by expressing the Saprolegnia diclina Δ17 desaturase gene ( sdd17m ) in M. alpina ST1358, an ω3‐desaturation activity‐defective mutant derived from M. alpina 1S‐4. Expression of the exogenous gene was confirmed by EPA accumulation in transformants at both 28 and 12°C. The EPA content in total lipids produced by transformants was over 20% at 28°C. Bench‐scale fermentation with a 5‐L jar fermentor showed that EPA content reached 26.4% of total fatty acids, and EPA production reached 1.8 g/L. This is the first study to report the accumulation of EPA in M. alpina at an ordinary temperature, and provide a platform technology for the industrial production of EPA using M. alpina as a promising source for EPA. Practical applications: This achievement shows the potential of M. alpina for industrial production of EPA at lower cost compared to conventional transgenic organisms such as plants and yeasts. The composition of fatty acids produced by M. alpina transformants was simple and did not contain unusual fatty acids compared with that of fish oils, so it may be acceptable for general consumers. Low‐cost, large‐scale, and high‐purity EPA supply by M. alpina will also lead to development of academic research on physiological functions of EPA and its derivatives. The oleaginous fungus Mortierella alpina accumulates eicosapentaenoic acid (EPA) only when cultivated at a low temperature (below 15°C). Here, we investigated EPA production at an ordinary temperature (28°C) by expressing the Saprolegnia diclina Δ17 desaturase gene ( sdd17m ) in M. alpina . The transformants with the sdd17m gene produced EPA (>20% in total lipids) at 28°C. Abstract : The oleaginous fungus Mortierella alpina accumulates eicosapentaenoic acid (EPA) only when cultivated at a low temperature (below 15°C). Here, we investigated EPA production at an ordinary temperature (28°C) by expressing the Saprolegnia diclina Δ17 desaturase gene ( sdd17m ) in M. alpina . The transformants with the sdd17m gene produced EPA (>20% in total lipids) at 28°C.